A membrane-free flow electrolyzer operating at high current density using earth-abundant catalysts for water splitting - Xiaoyu Yan (Nature Portfolio, 2021)
Seawater electrolysis is promising for grid-scale H2 production without freshwater reliance, but high energy costs and detrimental Cl chemistry reduce its practical potential. Here, authors developed an energy-saving hybrid seawater electrolyzer for chlorine-free H2 production and N2H4 degradation.